Elastic investigation of piers numbers effects in transverse direction on the stiffness of continuous and simply supported bridges - Naser, Ali Fadhil (Penerbit Universiti Kebangsaan Malaysia, 2021)
Piers were important structural members between superstructure and foundation of bridge which were designed to transfer and resist the vertical loads and horizontal loads (dead load of structure, traffic loads, water pressure, ice, and wind) to the foundation. The objective of this study was to evaluate the effect of number of piers in transverse direction (horizontal distance or spacing) between piers on the static and dynamic responses for two types of bridges structure which they include continuous and simply supported bridges. Static and dynamic analysis methods were adopted to analyse the bridges structures by using CSI-bridge software. The results of static analysis for two types of bridges models (continuous and simply supported) showed that the increasing of piers numbers had significant effects on the increasing of bridge structure stiffness by decreasing the downward vertical deflection due to service loads, increasing of the resistance of prestressed loads to service loads, and increasing of compression stresses. The results of time history analysis for two types of bridges models showed that the values of natural frequency were increased when the piers numbers were increased. Traffic load frequency (vibration frequency) values were decreased with increasing of bridge piers number because of the bridge structure had more stability. It can be concluded that the values of natural frequency were more than values of traffic load frequency, indicating that the bridges structures had enough stiffness and stability.